Effect of Corporate Financial Hedging, Risk Governance, Corporate Governance, Tax Avoidance on Firm value - Silva Wulandari; Susanti SE MM; Shella Rosananda; Amaliya Dinda Damara; Putu Monica Sari; Yesi Eka Evri Yanti; Gilang Ramadan (Prosiding International conference on Information Technology and Business (ICITB), 2022)
This research was conducted by looking at the phenomenon of recession that is predicted to occur in 2023 and the consideration of Covid-19 cases that have devastated  the economy in the country for several years. There are many companies that feel disadvantaged and a sharp decline in the value of their companies.   To  increase  company  value, company  owners improve company performance by  conducting  Corporate Financial Hedging, Risk Governance, Corporate Governance, Tax Avoidance.   So that the purpose of this study was formed, namely to determine the influence  of Corporate  Financial Hedging, Risk Governance, Corporate Governance, Tax Avoidance on the value of Firms.  The analysis method  is descriptive statistical and Multiple Regression analysis.Keywords: corporate financial hedging, risk governance, corporate governance, tax avoidance, firm value